Implementation Levels of Inquiry with Blended Learning to Improve Creative Thinking Skills in the Pandemic Era - Selly Feranie; Royhanun Athiyyah; Anggi Datiatur Rahmat; Dadang Machmudin; Nadiya Syafia Shani (Jurnal Penelitian Pendidikan IPA, 2023)
Current learning aims to improve students' skills to face 21st-century life. Creative thinking skills include 21st-century skills in innovation and technological development. This study aims to determine the improvement of students' creative thinking skills in the pandemic era using inquiry-based learning. This study uses a mixed method with an embedded design. The creative thinking skills test instrument is in the form of 14 open-ended questions developed based on the Scientific Creativity Structure Model compiled by Weiping Hu and Philip Adey. The analysis data using paired t-test. The results of statistical tests using paired t-tests showed a significant value of 0.000. Based on the decision-making criteria, if the significance value is less than 0.005, then Ho is rejected. The result can be interpreted as a significant difference between the pre-and post-test results. In addition, the increase in pretest-posttest scores was tested using n-gain and obtained a score of 0.55 in the medium category. Therefore, implementing levels of inquiry with blended learning on the light wave concept can improve the creative thinking skills in the medium category.